Municipal awareness as a tool for enhancing citizen satisfaction in municipal councils of Malaysia - Kasim, Rozilah; Bello, Muhammad Umar; Martin, David (Open Access Publishing Group, 2017)
This research study critically analysed the existing literatures on municipal awareness relevancy of LAs service delivery for the purpose of enhancing citizen satisfaction. The purpose of the study is the investigation of citizen satisfaction level of municipal services; analysis of the existing literatures on relationship between municipal awareness and citizen satisfaction. The Material and methods were carried out using secondary data and were meticulously and critically analysed to come up with reliable results. The study shows the relevancy of the public awareness, citizen satisfaction and municipal council performance in Malaysia. It is evidence in the research that citizen consent is importance before municipal services should be provided in the local community. The research study highlighted many discrepancies in many literatures related to the existing research study, evidence based analysis were carried out to buttress importance and significance of the related study to the research work. The literatures were reviewed to ascertain the current happening in the area of local government service delivery. The study shows that many municipal councils in Malaysia provide adequate and satisfactory services to their citizens’. The study also revealed that municipal council plays important role on citizen awareness of municipal service delivery. The study concludes that municipal service delivery can be enhanced through citizen awareness campaign, to sensitize the local community on various aspects of service delivery including maintenance of the facilities provided. The study also concludes that LAs lack of awareness section affects their performance in service delivery process. The study recommends that LAs need to consults the citizen for their needs and wants; awareness campaign need to be regularly carried out to maintain cordial relationship between LAs and their citizen; it is also recommended that municipal services should be delivered the needed services by the local inhabitants’ after duly consultation